1990
DOI: 10.1083/jcb.111.3.929
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosed beta-VLDL and LDL are delivered to different intracellular vesicles in mouse peritoneal macrophages.

Abstract: Hypercholesterolemic rabbit beta-VLDL and human LDL are both internalized by mouse peritoneal macrophages by receptor-mediated endocytosis. However, only beta-VLDL (which binds to the cells with a much higher affinity than LDL) markedly stimulates acyl-CoA/cholesterol acyl transferase (ACAT) and induces foam cell formation in these cells. As an initial step to test whether the two lipoproteins might be targeted to different organelles (which might differ in their ability to deliver cholesterol to microsomal AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 36 publications
6
87
1
Order By: Relevance
“…Second, the staining pattern of SMase in the cellular regions of both the normal aorta (ie, the endothelium) and lesions (ie, the intima) was not typical of 1 that was solely lysosomal, which usually appears as a perinuclear vesicular pattern. 65 Rather, some of the stain appeared on the outer edges of cells or bound to the pericellular matrix. In fact, even though our data suggest that the media of lesions is rather devoid of S-SMase, it is notable that this region showed poor staining of intracellular lysosomal SMase, which is an enzyme presence in all cells, including SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the staining pattern of SMase in the cellular regions of both the normal aorta (ie, the endothelium) and lesions (ie, the intima) was not typical of 1 that was solely lysosomal, which usually appears as a perinuclear vesicular pattern. 65 Rather, some of the stain appeared on the outer edges of cells or bound to the pericellular matrix. In fact, even though our data suggest that the media of lesions is rather devoid of S-SMase, it is notable that this region showed poor staining of intracellular lysosomal SMase, which is an enzyme presence in all cells, including SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from our (16,25,26) and other (27) laboratories have shown that foam cell-inducing lipoproteins undergo prolonged contact with the surface of macrophages, an event that may be important in the stimulation of the cholesterol esterification pathway (28). In this report, we examined the relationship in location between one such lipoprotein, ␤-VLDL, and ACAT.…”
Section: Figmentioning
confidence: 90%
“…Rhodamine-conjugated anti-rabbit and anti-chicken IgG were from Jackson ImmunoResearch Laboratories, Inc. (West Grove, PA), and Oregon green-conjugated antirabbit IgG was from Molecular Probes, Inc. (Eugene, OR). ␤-VLDL was prepared from the sera of rabbits fed a high fat, high cholesterol diet (2% cholesterol and 10% soy bean oil) as described previously (16) and conjugated to Texas Red (Molecular Probes, Inc.) according to the manufacturer's instructions. All other reagents were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the lysosomal degradation of LDL-derived apoB (14), ␤-VLDL-derived apoE was identified in widely distributed vesicles and showed a slow protein degradation in mouse macrophages (15,16). However, in the same cells, ␤-VLDLderived lipids were delivered to perinuclear, lysosomal compartments (17).…”
mentioning
confidence: 98%